Physico-Chemical Characetristics of Water from Bore Wells of an Industrial Town Bhilwara, Rajsthan: A Correlation Study - Hussain, J.; Sharma, K.C.; Hussain, I.; Ojha, K.G.; Vaidya, V.K. (Asian Journal of Chemistry, 2010)
Physico-chemical characteristics of water samples from 35 bore wells in the industrial town Bhilwara were studied. The values of 'r' (> 0.90) show significant positive correlation between electrical conductivity, total hardness, total dissolved solids, chloride and magnesium. The experimental values for parameter magnesium and total dissolved solids agree with predicted values and thus the correlation may be used for groundwater quality monitoring.